2004
DOI: 10.1161/01.cir.0000141369.50476.d3
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Organized Left Atrial Tachycardias Occurring After Pulmonary Vein Isolation

Abstract: Background-A proarrhythmic consequence of pulmonary vein (PV) isolation can be a recurrent organized left atrial (LA) tachycardia after ablation. This arrhythmia is frequently referred to as "left atrial flutter," but the mechanism and best ablation strategy have not been determined. Methods and Results-Isolation of arrhythmogenic PVs was initially performed by segmental ostial PV ablation guided by a circular mapping catheter in 341 patients. Patients whose predominant recurrent arrhythmia was a persistent or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
140
1
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 272 publications
(156 citation statements)
references
References 27 publications
7
140
1
5
Order By: Relevance
“…But it confirms data from previous observational studies showing that patients with AF recurrences almost always have conduction gaps and indicates the challenge of creating durable lesions by sequential radiofrequency current ablation. 24 The correlation between PV reconduction and AF recurrence underlines the important role of the PVs as shown in multiple observational studies [12][13][14][15][16][17][18][19] and in an experimental study. 25 In vitro data from optical mapping of a 2×2 cm 2 area of the PVs in isolated perfused dog hearts showed conduction slowing at the proximal part of the PVs, repolarization heterogeneity with the longest action potential duration at the PV endocardium when compared with the PV epicardium, and sustained focal discharge from the endocardial surface when stimulated with isoproterenol.…”
Section: Reconduction After Complete Pvi and Af Recurrencementioning
confidence: 87%
See 1 more Smart Citation
“…But it confirms data from previous observational studies showing that patients with AF recurrences almost always have conduction gaps and indicates the challenge of creating durable lesions by sequential radiofrequency current ablation. 24 The correlation between PV reconduction and AF recurrence underlines the important role of the PVs as shown in multiple observational studies [12][13][14][15][16][17][18][19] and in an experimental study. 25 In vitro data from optical mapping of a 2×2 cm 2 area of the PVs in isolated perfused dog hearts showed conduction slowing at the proximal part of the PVs, repolarization heterogeneity with the longest action potential duration at the PV endocardium when compared with the PV epicardium, and sustained focal discharge from the endocardial surface when stimulated with isoproterenol.…”
Section: Reconduction After Complete Pvi and Af Recurrencementioning
confidence: 87%
“…10,11 Further evidence came from patients with symptomatic AF recurrences after successful PV isolation (PVI), with limited data in asymptomatic patients. [12][13][14][15][16][17][18][19] These studies showed that patients with recurrent AF after PVI had reconduction from the PVs to the left atrium in ≤95% of cases. Closure of these conduction gaps with radiofrequency current led to reisolation of the PVs with only few AF recurrences.…”
Section: Kuck Et Al Ablation Strategies For Atrial Fibrillationmentioning
confidence: 95%
“…253,436,507,508,622,623, 624,625,630,870,871,995,996,997,998,999,1000,1001,1002 Most of these tachycardias originate in the LA, although RA cavotricuspid isthmus (CTI)-dependent flutters might also occur. Patients with a regular AT of new onset might complain of worsening symptoms due to a faster mean ventricular rate (frequently 2:1 ventricular response) than that during AF preablation.…”
Section: Early Reablationmentioning
confidence: 99%
“…All patients had experienced prior PVI targeting entry and exit block and elimination of non-PV triggers of AF as the end points of the initial procedure performed at our institutions. 7,8 Additional substrate-based ablation was not routinely deployed. If tolerated, all patients were routinely discharged on antiarrhythmic medication for at least 6 weeks after ablation.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] In this setting, the most common macroreentrant left AT is clockwise or counterclockwise reentry around the mitral valve. 3 Left atrial (LA) roof-dependent flutter is a common macroreentrant LA tachycardia that involves the LA roof and typically spins around ipsilateral pulmonary veins (PVs).…”
mentioning
confidence: 99%